2012
DOI: 10.1590/s0100-72032012001100005
|View full text |Cite
|
Sign up to set email alerts
|

Efeito da adição do biofeedback ao treinamento dos músculos do assoalho pélvico para tratamento da incontinência urinária de esforço

Abstract: ResumoOBJETIVO: Verificar o efeito da adição do biofeedback (BF) ao treinamento dos músculos do assoalho pélvico (TMAP) para o tratamento da incontinência urinária de esforço (IUE). MÉTODOS: Estudo piloto prospectivo, randomizado e controlado, com mulheres com IUE sem deficiência esfincteriana detectada ao estudo urodinâmico e que realizavam a correta contração dos MAP. Foram excluídas mulheres com doenças neuromusculares e com prolapso genital graus III e IV. Foram randomizadas 40 mulheres em Grupo Controle e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
1
11
0
3
Order By: Relevance
“… 24 Conversely, another of the studies found between group differences in favour of pressure biofeedback PFMT compared with PFMT in women with stress urinary incontinence on all but one King’s Health Questionnaire domain after 12 weeks (n=40). 25 A further trial by the researchers found that women with stress urinary incontinence (n=72) were no more likely to increase the frequency of home exercise after three months, irrespective of whether they had home PFMT with clinic pressure biofeedback, or home and clinic PFMT, and cure did not differ at nine months. 26 Electromyographic biofeedback with PFMT has, however, been found to statistically significantly improve pelvic floor muscle strength compared with PFMT alone for women with stress urinary incontinence (n=49).…”
Section: Discussionmentioning
confidence: 98%
“… 24 Conversely, another of the studies found between group differences in favour of pressure biofeedback PFMT compared with PFMT in women with stress urinary incontinence on all but one King’s Health Questionnaire domain after 12 weeks (n=40). 25 A further trial by the researchers found that women with stress urinary incontinence (n=72) were no more likely to increase the frequency of home exercise after three months, irrespective of whether they had home PFMT with clinic pressure biofeedback, or home and clinic PFMT, and cure did not differ at nine months. 26 Electromyographic biofeedback with PFMT has, however, been found to statistically significantly improve pelvic floor muscle strength compared with PFMT alone for women with stress urinary incontinence (n=49).…”
Section: Discussionmentioning
confidence: 98%
“…The digital palpation was not performed in seven articles and the musclulature was evaluated by electromyography [21,44] or perineometry [45 -49]. Among those using the MOS, six articles complemented their evaluation using the PERFECT method even if adapted [15,18,23,27,29,33].…”
Section: Discussionmentioning
confidence: 99%
“…This issue could be easily solved by using the MOS associated with the PERFECT method which, as can be observed, is the digital palpation assessment that is closest to what is recommended by IUGA and ICS [22]. However, it has been observed that only the knowledge of the PERFECT method is insufficient to guarantee its effective use, since two of the studies found reported its use with adaptations, excluding important steps such as endurance, repetitions and relaxation capacity [18,27]. Therefore, it is relevant to emphasize the importance of the awareness of clinical professionals about this fact, since, in addition to being recommended by IUGA and ICS, the information obtained during the evaluation favors the prescription of a PFMT considering the specificities of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The request was associated with digital vaginal palpation. This conduct is considered a verbal biofeedback that refers to the use of various audio-visual techniques that inform the patient about the activity of the striated muscles while trying to control the function of these muscles (26) .…”
Section: Discussionmentioning
confidence: 99%